PENDAMPINGAN SOSIALISASI PEMANFAATAN URINE SAPI SEBAGAI PUPUK ORGANIC CAIR TERHADAP EFISIENSI BIAYA PERTANIAN - Yeny Fitriyani; Miswan Ansori; Tutik Rofiqoh (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
Assistance in the socialization of cow urine as liquid organic fertilizer can be used for agricultural cost efficiency and has its socio-economic value for the community. In this service activity, counseling assistance and socialization assistance were carried out to residents, especially members of the Pangudi Makmur farmer group in Dalangan Hamlet. The benefits of using cow urine can reduce agricultural costs and reduce pollution caused by urine. Liquid organic fertilizer, if used on plants, will reduce dependence on chemical fertilizers so that the quality of the plants is better. Students carry out service implementation with residents who are expected to develop the community's economic capacity. The method used in this approach uses participatory, action, and research (PAR) methods. Making cow urine as organic liquid fertilizer can generate business ideas and solutions to save agricultural costs (efficient).